Análisis de la incorporación de sistemas fotovoltaicos tipo red en el alimentador centro Babahoyo 13.8kV de CNEL EP unidad de negocios los Ríos - Macias Salazar, Frixon Samuel (2022)
The electrical power system has always been in constant analysis to improve its operation and provide a quality service to users, always at the lowest possible cost. The implementation of distributed generation to the grid is a necessary advance in the electrical power system. These generation centers are characterized by having small and medium scale dimensions, in this way they can be easily installed near load centers with a fairly low environmental impact compared to conventional generation centers. The Distributed generation systems for self-supply (SGDA) carry on with the effects that are analyzed in this project in the electrical distribution network, using the CENTR0- BABAHOYO 13.8kV feeder of CNEL EP-Business Unit Los Ríos, to obtain the changes that the implementation of the SGDA entails with the help of the software CYME, where photovoltaic generation systems will be used. For this analysis, a study of environmental conditions in the city of Babahoyo was carried out, where parameters such as irradiance, peak solar time and temperature were obtained. For the sizing, the consumption of certain users will be taken as a sample and the photovoltaic generation systems will be designed based on the demand of these users individually. The results achieved with the implementation of SGDA were presented, which they denote the improvements obtained in the electrical grid, and these were because the use of 665 SGDA. In addition, these improvements make the losses in the feeder lines get decreases due to the demand in the feeder line is reduced, and in the same way the losses due to energy transport is reduced.